# Solve the followi

Given x2 – 4x + 7 = 0

x2 – 4x + 4 + 3 = 0

x2 – 2(x)(2) + 22 + 3 = 0

(x – 2)2 + 3 = 0 [ (a – b)2 = a2 – 2ab + b2]

(x – 2)2 + 3 × 1 = 0

We have i2 = –1 1 = –i2

By substituting 1 = –i2 in the above equation, we get

(x – 2)2 + 3(–i2) = 0

(x – 2)2 – 3i2 = 0 Since a2 – b2 = (a + b)(a – b), we get    Thus, the roots of the given equation are .

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

–x2 + RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the fRD Sharma - Mathematics

Solve:
<
RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

x2 + 1RS Aggarwal - Mathematics